Modelling property markets using neural network - Phang, Kok Chiang. (2012)
This paper aims to look at property market in Singapore and the factors that affect the property prices for both private and public resale housing. It uses Neural Network techniques to analyse the impact of macroeconomic factor, supply and demand factors, government policy and land usage on price movement of the various housing sectors locally. The paper investigates the effectiveness of a number of neural network architectures in predicting property housing prices.